La política fiscal en Chile. Configuración y problemáticas de la Hacienda pública en el marco del proceso de construcción estatal, 1817-1850 - Elvira López Taverne (Les Cahiers ALHIM)
The organization of the public finances is one of the first challenges facing the governments of former Spanish colonies in America. Financial management will prove to be crucial both in times of war and peace in the 1800’s. This article analyzes the guiding principles of financial organization in independent Chile, and the projects and problems faced by its new leadership. Although the burden of recent war and economic crisis are critical in the 1820’s, foreign trade provides an early reorganization of fiscal revenue in the 30’s. It also analyzes the guiding principles of financial organization under conservative governments, who claim credit for this process of economic developement and stabilization, which is exceptional as compared to other Spanish colonies.